2006
DOI: 10.1523/jneurosci.0175-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Basis for Whisker Deprivation-Induced Synaptic Depression in Rat Somatosensory Cortex

Abstract: Whisker deprivation weakens excitatory layer 4 (L4) inputs to L2/3 pyramidal cells in rat primary somatosensory (S1) cortex, which is likely to contribute to whisker map plasticity. This weakening has been proposed to represent long-term depression (LTD) induced by sensory deprivation in vivo. Here, we studied the synaptic expression mechanisms for deprivation-induced weakening of L4-L2/3 inputs and assessed its similarity to LTD, which is known to be expressed presynaptically at L4-L2/3 synapses. Whisker depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 70 publications
11
123
5
Order By: Relevance
“…In contemporaneous experiments, Bender et al (15,31) showed in layer 2/3 neurons of rat barrel cortex that STD-LTD, also occluded by whisker deprivation, is similarly inhibited by APV and AM251. Thus, a reasonable conclusion is that LFS and spike-timing protocols induce layer 2/3 LTD in sensory cortex by a common mechanism that is also accessed by sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contemporaneous experiments, Bender et al (15,31) showed in layer 2/3 neurons of rat barrel cortex that STD-LTD, also occluded by whisker deprivation, is similarly inhibited by APV and AM251. Thus, a reasonable conclusion is that LFS and spike-timing protocols induce layer 2/3 LTD in sensory cortex by a common mechanism that is also accessed by sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reasonable conclusion is that LFS and spike-timing protocols induce layer 2/3 LTD in sensory cortex by a common mechanism that is also accessed by sensory deprivation. However, Bender et al (15,31) showed that intracellular MK801 (1 mM) had no effect on STD-LTD induction, whereas it was blocked by antagonists of metabotropic glutamate receptor 5 (mGluR5). They conclude that the relevant source of postsynaptic calcium for induction of STD-LTD is release from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, sensory deprivation alters STP at a variety of synapses. However, the effect of sensory deprivation on STP is often inconsistent even for the same synapse type, with specific types of sensory deprivation promoting facilitation but others increasing depression [31 •• , [39][40][41][42][43]. A number of experimental factors, including the nature and age of deprivation [39,44] Similarly, preNMDARs influence STP at synapses from L4 neurons onto L2/3 pyramidal neurons, but not at L2/3 intralaminar synapses [47].…”
Section: Synapse-type-specific Short-term Plasticitymentioning
confidence: 99%
“…3F), the time constant of which is inversely related to P r . The decay kinetics were fit by a double exponential, and the fast time-constant of decay (τ f ) compared across groups (26,27). MK-801 blockade led to a slower τ f , implying a lower P r in KO cells [WT: 0.78 ± 0.32, n = 7; KO: 1.86 ± 0.24, n = 7 (stimuli); P < 0.05] (Fig.…”
Section: La Neurons From Ko Mice Exhibit Both Post-and Presynaptic Dementioning
confidence: 99%